2016
DOI: 10.3892/etm.2016.3139
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety comparison of DL-3-n-butylphthalide and Cerebrolysin: Effects on neurological and behavioral outcomes in acute ischemic stroke

Abstract: Abstract. Cerebrolysin and DL-3-n-butylphthalide (NBP) have each shown neuroprotective efficacy in preclinical models of acute ischemic stroke (AIS) and passed clinical trials as therapeutic drugs for AIS. The present study was a clinical trial to assess and compare the efficacy and safety of NBP and Cerebrolysin in the reduction of neurological and behavioral disability following AIS. A randomized, double-blind trial was conducted with enrolment of 60 patients within 12 h of AIS. In addition to routine treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“… MRI-1 [ 9 ] MRI-2 [ 10 ] Amiri-Nikpour et al 2014 [ 11 ] Xue et al 2016 (individual patient data provided by authors for dropout inclusion) [ 12 ] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… MRI-1 [ 9 ] MRI-2 [ 10 ] Amiri-Nikpour et al 2014 [ 11 ] Xue et al 2016 (individual patient data provided by authors for dropout inclusion) [ 12 ] …”
Section: Methodsmentioning
confidence: 99%
“…For the present meta-analysis, all sites were included capturing the aggregate data from the integrated clinical study report. For study Xue 2016 [ 12 ], raw data of dropouts were provided by the authors in order to allow LOCF analysis. Besides the sources listed above, no further data have been provided by authors of abstracts or unpublished but registered studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L-3-n-Butylphthalide (NBP) is originally extracted from celery seeds, and was approved for the treatment of ischemic stroke by China Food and Drug Administration (CFDA) in 2002, and clinical studies have demonstrated its efficacy and safety (Xue et al 2016 ). Mechanisms contributing to its efficacy include increasing axonal growth, promoting neurogenesis and neuroplasticity, alleviating oxidative stress, mitigating neuronal injury and suppressing apoptosis of neuronal cells (Sun et al 2017 ; Yang et al 2015 ; Zhang et al 2016a ; Zhao et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the DL-3-n-butylphthalide (NBP) may act by improving mitochondria function and energy metabolism ( 39 ), decreasing oxidative damage and apoptosis ( 40 ), reducing inflammatory responses ( 41 ), and enhancing regional blood flow and angiogenesis ( 42 ) to protect against ischemic brain damage and to result in reduction of infarct volume ( 39 , 43 ). Clinical trials have also shown that NBP can improve outcomes of patients with stroke ( 44 , 45 ). In addition to NBP, statins ( 46 , 47 ), citicoline ( 48 ), and stem cells ( 49 ) are also purported to have multiple mechanisms of action for acute ischemic stroke.…”
Section: Neuroprotection Historymentioning
confidence: 99%